Iceland´s parliamentary elections in 2009 and their impact on foreign political development of the country - Hovorkova, K. (2016)
Historically, Iceland was one of the most reluctant countries regarding the membership in the European Union. With a stable political and economic situation, Iceland became member of economic organizations – the EFTA and the EEA, in order to gain immediate economic benefits, to not limit its traditional fishery industry and growing financial sector and to maintain the national sovereignty. However, this attitude has changed after the outbreak of the global financial crisis in Iceland and collapse of the country´s economy caused significant changes in political situation. With ongoing protests early parliamentary elections in 2009 took place. The election results and the dealing with the economic crisis in the country was the most significant turnover in Iceland in recent years due to traditional EU reluctance and usual center or center-right coalition in Althing. Therefore, the aim of this paper is to analyze parliamentary elections in Iceland in 2009 and the impact of election results on the foreign political development of the country. We will also focus on changes in preferences of political parties in Althing, as well as on the politics of the EU integration. With the deduction method we will conclude how the negotiation process and the economic as well as political situation influenced the slowdown in the implementation of the country´s political strategy – membership in the European Union. Исторически, Исландия была одной из самых несклонных стран к членству в Европейском союзе. В стабильной политической и экономической ситуации, Исландия стала членом экономической организации – ЕАСТ и ЕЭП, для того чтобы получить экономические выгоды, при этом не ограничивающие ее традиционное рыбное хозяйство, рост финансового сектора и поддержание национального суверенитета. Однако это отношение изменилось после начала глобального финансового кризиса в Исландии и развал экономики страны вызвал существенные изменения в политической ситуации. После продолжительных акций протеста в 2009 г. состоялись досрочные ...